Brand love Toward Brand Loyalty of Telehealth App’s - Praswati, Aflit Nuryulia; Ratna Ningsih, Pertiwi (Universitas Muhammadiyah Surakarta, 2024)
The Covid-19 pandemic has underscored the critical role of telehealth services in healthcare delivery, particularly in minimizing the risk of cross-contamination from close contact. Proactively integrating telehealth services, rather than relying on reactive measures, is likely to provide substantial long-term benefits and assist with daily healthcare challenges and emergencies. This study aims to identify the factors that affect the loyalty of telehealth service users, focusing on brand experience, brand love, brand trust, and brand equity. The study utilized a sample of 110 respondents, selected through purposive sampling, requiring participants to have used a telehealth application at least once. Data analysis was conducted using the Structural Equation Model (SEM) with Partial Least Square (PLS) methodology, utilizing SmartPLS 3.0 software. Findings from the study reveal that brand experience, brand love, brand trust, and brand equity all have a positive and significant impact on brand loyalty among telehealth application users.